Influence of zinc oxide nanoparticles on flashover voltage of unsaturated polyester resin-based composites for electrical insulators - Rihan, M.; Ghazzaly, A.; Fahmy, A. H.; Ebnalwaled, A. A.; Nasrat, L. S. (Національний технічний університет "Харківський політехнічний інститут", 2026)
Polyester-based composites are increasingly used in electrical applications for their insulation, mechanical, and thermal properties. Nanofillers have shown promise in enhancing the properties of polymer-based composites. Goal. This study aims to improve the flashover voltage of unsaturated polyester resin (UPR)-based composites by incorporating zinc oxide (ZnO) nanoparticles.

Композити на основі поліестеру все частіше використовуються в електротехніці завдяки своїм ізоляційним, механічним та тепловим властивостям. Нанонаповнювачі виявилися перспективними для покращення властивостей композитів на основі полімерів. Мета. Це дослідження спрямоване на підвищення напруги пробою композитів на основі ненасиченої поліефірної смоли (UPR) шляхом включаючи наночастинок оксиду цинку (ZnO).
Keywords: unsaturated polyester resin; zinc oxide; filler; nanocomposites; flashover voltage; curve fitting technique; ненасичена поліефірна смола; оксид цинку; наповнювач; нанокомпозити; напруга пробою; метод апроксимації кривої